2010
DOI: 10.1186/1471-2199-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of endogenous control genes for normalisation of real-time quantitative PCR data in colorectal cancer

Abstract: BackgroundGene expression analysis has many applications in cancer diagnosis, prognosis and therapeutic care. Relative quantification is the most widely adopted approach whereby quantification of gene expression is normalised relative to an endogenously expressed control (EC) gene. Central to the reliable determination of gene expression is the choice of control gene. The purpose of this study was to evaluate a panel of candidate EC genes from which to identify the most stably expressed gene(s) to normalise RQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 42 publications
3
57
0
4
Order By: Relevance
“…After comparing various housekeeping genes such as GAPDH, β-2 microglobulin, 18s ribosomal RNA, etc., some researchers have reported HPRT as the most consistent endogenous control (de Kok et al, 2005). Meanwhile, other researchers have reported HPRT levels to be significantly lower than other controls in cancer tissue (Kheirelseid, Chang, Newell, Kerin, & Miller, 2010). Finally, other studies have reported HPRT as an unsuitable standard in certain cell types due to varying expression in response to growth factor stimuli (Murphy & Polak, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…After comparing various housekeeping genes such as GAPDH, β-2 microglobulin, 18s ribosomal RNA, etc., some researchers have reported HPRT as the most consistent endogenous control (de Kok et al, 2005). Meanwhile, other researchers have reported HPRT levels to be significantly lower than other controls in cancer tissue (Kheirelseid, Chang, Newell, Kerin, & Miller, 2010). Finally, other studies have reported HPRT as an unsuitable standard in certain cell types due to varying expression in response to growth factor stimuli (Murphy & Polak, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These include 5 microRNAs (miR-23a, miR-200c, miR-26a, miR-1979, and let7a) which were chosen based on a cervical microRNA microarray expression data, two microRNAs (miR-191 and miR-103) which had be reported to be the most stable reference RNA targets in microRNA RT-qPCR studies (Peltier and Latham, 2008), 5S rRNA (121 nt) and U6 snRNA owing to their purported expression stability and use in several published microRNA RT-qPCR studies (Vandesompele et al, 2002;Peltier and Latham, 2008;Kheirelseid et al, 2010). We filtered the microRNA microarray expression data (form 6 HR-HPV negative cervical normal tissues and 6 HR-HPV positive cancer tissues) according to three criteria: (1) microRNA must be highly expressed in most of the samples; (2) microRNA must be consistently expressed (measured by the modified z-score), with a small coefficient of variation (CV); (3) only one representative microRNA was considered from a given family.…”
Section: Putative Reference Rna Targets and Primer Designmentioning
confidence: 99%
“…PDCD4 expression levels were normalised to PPIA and β2M expression levels [25]. Percent PCR amplification efficiencies (E) for each assay were calculated as E = (10-1/slope -1) × 100, using the slope of the semi-log regression plot of Ct versus log input of cDNA (10-fold dilution series of five points) A threshold of 10% above or below 100% efficiency was applied.…”
Section: Rna Extraction and Relative Quantification Of Mirna And Mrnamentioning
confidence: 99%